Composite electrolytes based on electrospun PVDF and ionic plastic crystal matrices for Na-metal battery applications. (14th April 2021) - Makhlooghiazad, Faezeh; Nti, Frederick; Sun, Ju; Mendes, Tiago Correia; Malunavar, Sneha Subhas; Pringle, Jennifer M; Forsyth, Maria
Abstract: Sodium ion batteries are widely considered to be a feasible, cost-effective, and sustainable energy storage alternative to Lithium, especially for large-scale energy storage applications. Next generation, safer electrolytes based on ionic liquid (IL) and organic ionic plastic crystals (OIPCs) have been demonstrated as electrochemically stable systems which show superior performance in both Li and Na applications. In particular, phosphonium‐based systems outperform most studied nitrogen‐based ILs and OIPCs. In this study triisobutyl(methyl)phosphonium bis(fluorosulfonyl)imide ([P1i444 ][FSI]) OIPC mixed with 20 mol% of NaFSI or NaTFSI were combined with an electrospun polyvinylidene fluoride (PVDF) support to create self-standing electrolyte membranes, and their thermal phase behaviour and ionic conductivity were investigated and compared with the bulk electrolytes. The ability of the solid-state composite electrolytes to support the cycling of sodium metal with good efficiency and without breakdown were examined in sodium metal symmetrical coin cells. The sodium transference number was determined to be 0.21. The electrochemical performance of Na/Na3 V2 (PO4 )3 cells incorporating the composite electrolytes, including good cycling stability and rate capability, is also reported. Interestingly, the mixed anion systems appear to outperform the composite electrolyte containing only FSI anions, which may relate to electrolyte interactions with the PVDF fibres.